The Effectiveness of Implementing Good University Governance at Universitas Negeri Padang - Alhadi, Zikri; Putri, Putri; Eriyanti, Fitri; Yusran, Rahmadani; Riandini, Ory (Journal Public Policy, 2024)
The purpose of this article is to describe the research findings in the form of the effectiveness of Universitas Negeri Padang governance in achieving good university governance (GUG); researchers describe how the implementation of governance in achieving a GUG. Further research objectives are to look at Universitas Negeri Padang's governance and the supporting and inhibiting factors in realizing the effectiveness of the governance of Universitas Negeri Padang in achieving good university governance. This research uses a qualitative approach with descriptive methods that use purposive sampling techniques in the selection of informants. Data collection was carried out using observation techniques, interviews, and documentation. From the research results, it seems that Universitas Negeri Padang's governance is deep in achieving good university governance, which has not been fully effective. Then, a substantive conclusion is drawn that, specifically, the implementation of the governance of Universitas Negeri Padang management in carrying out the principles of accountability, transparency, and effectiveness in achieving GUG implementation still needs to be improved and strengthened its application. The importance of this research, in alignment with the principles of good university governance, lies in its potential to motivate higher education institutions to enhance the standards of tertiary governance in congruence with the pre-established vision and mission